Kebijakan Kepala Madrasah dalam Penguatan Mutu Pendidikan Islam Berbasis Digital: Studi Kasus di MTs Raudatul Muttaqin Dukuh Sari - Hendra; Muhammad Ridwan Maulana; Sabarudin; Malikha Kumala Nabila; Alwan wildani; Gede Moh Syahreza (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2025)
Purpose – Madrasah principals play a strategic role in improving the quality of Islamic education amidst the rapid changes in the digital era. This study aims to describe the policies of the Principal of Madrasah Tsanawiyah Raudatul Muttaqin Dukuh Sari in improving the quality of Islamic education in the digital era, while also analyzing the contextual implementation of these policies. Methods–This research employed a qualitative approach with a case study method. Data were collected through semi-structured interviews, participant observation, and documentation with purposively selected research subjects, including madrasah principals, teachers, and related educational staff. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldaña through the stages of data reduction, data presentation, and conclusions. Findings –The results indicate that the madrasah principal's policies in improving the quality of Islamic education are implemented through several strategies, namely strengthening teacher competencies in technology, implementing digital media-based learning, strengthening academic supervision, and building synergies with various parties. Furthermore, the madrasah principal also strives to maintain a balance between the use of technology and strengthening Islamic values ​​within the madrasah environment. This policy has been proven to support the creation of more effective, interactive, and adaptive learning, while strengthening students' religious character.